The Construction of the Neo-colonial State: The Nicaraguan Encounter with Dollar Diplomacy - Gobat, Michel (2009)
This article describes the political and economic practices that characterized the dollar diplomacy in Nicaragua. It illustrates how the novel U.S. economic project, intended to modernize the Latin American States, turned out to be a feudal, anti-modern project, from the point of view of Nicaraguan upper classes. Some of the unforeseen effects of this imperialist policy let the author show that the analysis of economic and social conditions carried out by a privileged section of society may conceal or misrepresented the economic and social conditions of other groups. Doing this the privileged sectors of society present their own experience as a generalized experience.